(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study explores the implementation of transformational leadership in two rural Indonesian schools SMA Negeri 3 Tarutung and SMA Negeri 1 Siborongborong through a descriptive qualitative approach conducted from August 2024 to April 2025. Data were gathered via interviews, observations, and document analysis, and validated using triangulation of sources, techniques, and time, while analysis followed the Miles and Huberman interactive model. The findings show that both principals demonstrated the four dimensions of transformational leadership as proposed by Bass: idealized influence through discipline and exemplary conduct, inspirational motivation through shared visions and slogans such as “Solid Berbehan”, intellectual stimulation by fostering innovation and scientific activities, and individualized consideration through personal mentoring and talent mapping. While SMA Negeri 3 Tarutung’s strengths lie in leadership discipline and teacher innovation but face challenges in student communication, SMA Negeri 1 Siborongborong demonstrates inclusive leadership and collaboration, though decision-making processes are less observable. Externally, parental support, school committees, and community expectations strongly reinforce leadership effectiveness. The novelty of this research lies in its comparative analysis of transformational leadership in rural Indonesia, highlighting how local culture and stakeholder dynamics shape school leadership practices. It contributes to the literature by providing contextualized insights into the implementation of transformative leadership and offers practical implications for school leaders and policymakers seeking to enhance leadership performance through innovation and community engagement.